2019
DOI: 10.1515/jpem-2018-0330
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting intramuscular ACTH stimulation test for the diagnosis of secondary adrenal insufficiency in children

Abstract: Background The diagnosis of adrenal insufficiency (AI) is based on the basal and stimulated levels of serum cortisol in response to the short Synacthen test (SST). In patients with secondary AI (SAI) due to hypothalamic-pituitary-adrenal (HPA) axis defects, the SST has been validated against the insulin tolerance test (ITT), which is the gold standard. However, injection Synacthen is not easily available in some countries, and endocrinologists often use Acton-Prolongatum (intramuscular [IM] long-acting adrenoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A previous study from our centre has reported a high diagnostic accuracy (sensitivity100%; specificity88%) for stimulated serum cortisol levels using Acton Prolongatum in subjects with suspected AI in comparison with the SST 22,23 . Other investigators from India have also assessed the performance of Acton prolongatum stimulated serum cortisol measurements in healthy children and adults against SST and ITT 19,35,36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study from our centre has reported a high diagnostic accuracy (sensitivity100%; specificity88%) for stimulated serum cortisol levels using Acton Prolongatum in subjects with suspected AI in comparison with the SST 22,23 . Other investigators from India have also assessed the performance of Acton prolongatum stimulated serum cortisol measurements in healthy children and adults against SST and ITT 19,35,36 …”
Section: Discussionmentioning
confidence: 99%
“…22,23 Other investigators from India have also assessed the performance of Acton prolongatum stimulated serum cortisol measurements in healthy children and adults against SST and ITT. 19,35,36 To the best of our knowledge, this is the first study to assess the diagnostic accuracy of salivary cortisol response to long-acting porcine sequence ACTH for diagnosing AI. 24 The reported crossreactivity with cortisone was only 6.58%.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of our study include absence of dose titration of porcine ACTH and lack of an assay specific cut-off for Synacthen-stimulated serum cortisol in our laboratory. As opposed to previous studies using 25 units of Acton Prolongatum ® for the APST, this study used 30 units considering the ease of dispensing from a 5 mL vial containing 300 units (6,12,13). No adverse events were observed with Synacthen or Acton Prolongatum in the present study.…”
Section: :6 643 Clinical Studymentioning
confidence: 98%
“…The effectiveness of the im-ACTH test in detecting central AI cases has also been investigated ( 8 ). Cases with short stature and at risk of having multiple hormone deficiencies and tested with ITT were evaluated.…”
Section: Discussionmentioning
confidence: 99%